Revision Total Knee Arthroplasty Using a Constrained Condylar Knee Prosthesis Combined with a Posterior Stabilized Articular Surface - Tsai, Shang-Wen; Chen, Cheng-Fong; Wu, Po-Kuei; Chen, Chao-Ming; Chen, Wei-Ming (The Journal of Knee Surgery, 2018)
Intraoperative assessment of valgus–varus stability is crucial for choosing articular surfaces with different levels of constraint. Legacy constrained condylar knee (CCK) prostheses are readily available to assemble and use with a CCK articular surface or a posterior stabilized (PS) articular surface in revision knee arthroplasty surgeries. We wanted to validate outcomes of revision total knee arthroplasty (TKA) using legacy CCK prostheses combined with a PS articular surface. Thirty-seven patients were enrolled and followed up for more than 2 years. Range of motion (ROM), the Knee Society score (KSS), the Knee Society functional score (KSS-F), and the Western Ontario and McMaster Universities Arthritis Index (WOMAC) were used to evaluate outcomes. Follow-up was a mean of 86.5 months (range: 28–152 months). The mean age of the participants was 69.8 years (range: 31–86 years). The mean ROM was 110.5 degrees, the KSS was 86.2 points, the KSS-F was 68.3 points, and the WOMAC score was 22.6 points. Seven participants had implant failures: five because of delayed infections and two because of posterior dislocations. In conclusion, revision TKA using a CCK prosthesis combined with a PS articular surface might provide satisfactory mid-term outcomes. Delayed infection was the most common cause of implant failure. Dislocation might occur in middle-old or older patients despite careful intraoperative examination of valgus–varus stability, extension–flexion gap balancing, and signs of recurvatum.
Keywords: articular surface; constrained condylar knee; inserted; posterior stabilized; revision total knee arthroplasty